Evaluation of land suitability for corn (Zea Mays, L) in Kualuh Selatan District, North Labuhanbatu Regency - Harahap, Fitra Syawal; Walida, Hilwa; Sidabuke, Simon; Arman, Iman (Universitas Pekalongan, 2024)
The approach or method for evaluating land resource potential is a method of land evaluation. The expected production value that may be obtained, as well as the information and/or direction of land use required, will be provided by the results of the land evaluation. .Evaluation of the characteristics of the level of land suitability in the area is carried out to analyze improvement efforts aimed at increasing productivity and produce maps of actual land suitability and potential land suitability for superior commodities in the sub-district. Land use in South Kualuh District needs to be supported by land suitability information. Survey methods used. Land units are based on land maps, slope, elevation and land cover. The process of comparing (matching) is an analysis method.The results of the research show that the level of land suitability for corn plants. The condition of the actual land to become potentially suitable for cultivation in Kualuh Selatan District for corn plants is the limiting factor in nutrient availability (na), temperature regime (tc), rooting media (rc), nutrient retention (nr ) and the danger of erosion (eh). Improvement efforts that can be made include making drainage, liming CaCO3, adding organic material, making terraces or planting parallel to the contour and fertilizing. The temperature regime cannot be repaired